Damped vibrations of alpine skis on inelastic foundations - Eberle, R.; Kaps, P.; Oberegger, U. F.; Heinrich, D.; Mössner, M.; Schindelwig, K.; Niederkofler, A.; Nachbauer, W. (Science and Skiing V. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2012)
INTRODUCT1ON: In Alpine skiing, an effective damping of ski vibrations might improve the performance considerably. In the present study vibrations of a real ski are investigated both theoretically and experimentally. The ski was modeled as beam using exact geometric data for length, width, thickness, camber, the measured flexural stiffness, and a constant density [2]. Several situations were investigated: 1.) free vibrations of ski shovel and tail, ski center clamped 2.) vibrations of ski shovel and tail, ski loaded by a skier on an inelastic foundation 3.) vibrations caused by drop jumps of a skier from a height of 20-30 cm with an unedged ski.